2017
DOI: 10.3897/compcytogen.v11i3.13124
|View full text |Cite
|
Sign up to set email alerts
|

Diversification of the P genome among Agropyron Gaertn. (Poaceae) species detected by FISH

Abstract: The genomes of five Agropyron Gaertner, 1770 species were characterized using all potential di- or trinucleotide simple sequence repeat (SSR) motifs and four satellite DNA repeats as fluorescence in situ hybridization (FISH) probes. The sites of 5S and 45S rDNA were relatively conserved among the diploid and tetraploid species. A number of sites for the dinucleotide SSRs AC, AG, and pSc119.2 was detected in all investigated species except A. mongolicum Keng, 1938. Several different trinucleotide SSRs were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Most of these species showed quite stable 1C DNA content values across the transect, except Artemisia frigida and Agropyro cristatum . Previous studies had reported the 1C value for diploid A. frigida(2.63 pg) and A. cristatum (6.49 pg) (Garcia et al 2008;Said et al 2018), with their polyploid species being identified in nature (Wan et al 2011;Zhao et al 2017). In our case, the measured 1C values indicated that A. frigida andA.…”
Section: Plant Genome Size Measurementssupporting
confidence: 59%
“…Most of these species showed quite stable 1C DNA content values across the transect, except Artemisia frigida and Agropyro cristatum . Previous studies had reported the 1C value for diploid A. frigida(2.63 pg) and A. cristatum (6.49 pg) (Garcia et al 2008;Said et al 2018), with their polyploid species being identified in nature (Wan et al 2011;Zhao et al 2017). In our case, the measured 1C values indicated that A. frigida andA.…”
Section: Plant Genome Size Measurementssupporting
confidence: 59%
“…The nature of the polyploid genome of A. cristatum and the origin of its P genome(s) have not yet been clarified. Schulz-Schaeffer et al (1963) proposed the segmental allopolyploid nature of tetraploid and hexaploid A. cristatum , while other authors consider the tetraploid A. cristatum as autopolyploid, originating from the diploid A. cristatum (Taylor and McCoy 1973; Vogel et al 1999; Zhao et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Agropyron species are considered as highly valuable sources to improve the crop resistance to biotic and abiotic stresses as well as quality and yield‐related traits (Ceoloni et al, 2015). One of the most widely spread species is crested wheatgrass, which is distributed in Eurasia (Dewey, 1984; Yang et al, 2014; Zhao et al, 2017). The species, and the tetraploid form in particular, also referred to as desert crested wheatgrass [ A. desertorum (Fisch.…”
mentioning
confidence: 99%